Separation of Autonomous Function from Cell Density in Non-Immunogenic Hyperthyroidism - Als, Claudine; Rosier, H.; Listewnik, Maria (Nuklearmedizin - NuclearMedicine, 1996)
Regional autonomous cell mass (Q: cell density ratio) and function (T: toxicity index) were compared by double isotope parametric thyroid scintigraphy (Als et al., Nucl. Med. 1995; 34) in 53 patients with non-immunogenic hyperthyroidism before and after radioiodine therapy (aRIT) and showed a break-down (medians) of Q: 4.3→1.0 (toxic adenomas: TA), 2→1.1 (multifocal functional autonomies: MFA) (p <0.0001) as of T: 96→1.7 (TA), 15→1.1 (MFA) (p <0.001). Five functional aRIT patterns resulted: euthyroidism (n = 37, 70%), at half with scarred/non-scarred autonomous areas (low/higher T, respectively), primary hypothyroidism (n = 4), residual hyperthyroidism (n = 7), secondary hyperthyroidism (n = 5). The last two groups with persistent subnormal TSH values were clearly separated by divergent T, thyroxine and triiodothyronine levels. A resulting T >1 may represent a clinically sub-critical mass of residual autonomous tissue. This new technique facilitates individual prethera-peutic evaluations and aRIT quality control.
Keywords: Non-immunogenic hyperthyroidism; toxic adenoma; multifocal functional autonomy; toxic nodular goitre; radioiodine treatment; 123l; 99mTc-hexamibi; quantitative thyroid scintigraphy; double isotope parametric subtraction scintigraphy; shrinkage of cell mass; euthyroidsm